Alien vs Bad Guys The Bad Guys - Aaron Blabey (Lindfield, Australia Scholastic Australia, 2017)
One by one, the Bad Guys are vanishing. Taken by a creature with way too many teeth and far too many bottoms. Is this the end? Maybe. But will it be funny? You bet your butts it will!
Keywords: Humorous Fiction -- Humorous Fiction